Drgania belki lepkosprężystej o skończonej długości i swobodnych końcach na podłożu sprężystym wymuszone przesuwającą się siłą - Borowik, S.; Szcześniak, W. (Engineering Transactions, 1969)
In this paper the solution is given of vibration forced by a bodyless load moving with a constant velocity for a viscoclastic beam of finite length and free ends on an elastic base. The solutions were formed out using the orthogonalization method with the eigenfunctions of the boundary problem. From the analysis included it results that the critical velocity of the load depends upon both theinternal damping (internal friction) and the phenomenological damping in the case, and that boththese dampings significantly influence the amplitude of vibration.